Draft Annual Plan 1980-81 Vol-2 (Brief Memorandum along with G.N. Statements) Haryana State - Planning Commission (Planning Commission, 1979)
The running Commission has approved the size or Haryana’s Five Year Plan 1978-83 at Rs 1450.00 crores. During the first year viz 17997, 8- an expenditure of Rs 193.93 crores has been incurred.
Planning Department, Haryana Government